IDENTIFIKASI WAJAH UNTUK MEMBUKA PINTU MENGGUNAKAN CONVOLUTIONAL NEURAL NETWORK - Muhamad Irsan; Wahyu Abiyoto; Dadang Sujana (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2021)
In this face identification, the researcher feels the lack of effectiveness for access to doors that still use fingerprints. With this kind of identification, it will be straightforward to prevent theft. Face identification is a process where we know someone by looking at their face. In face identification for door access using the convolutional neural network method and Library, Open Computer Vision using the Python programming language and this was made using several components, namely a 5mp camera as face identification, Raspberry pi3 as a microprocessor, LCD monitor, ULN 2003 driver and Stepper motor as a tool. Automatic door mover, Push button to move the door from the inside. This tool can detect faces by verifying faces with the closest distance of 50 meters to 150 meters and to an accuracy of 83.20% with a period of 3 seconds to move the automatic sliding door by receiving facial data from the raspberry to the 2003 ULN driver to move the stepper motor with Lay 5 seconds, rotate clockwise and turn around again counterclockwise